The relationship between the dietary inflammatory index (DII®) and incident depressive symptoms: A longitudinal cohort study - Shivappa, Nitin; Hébert, James R.; Veronese, Nicola; Caruso, Maria Gabriella; Notarnicola, Maria; Maggi, Stefania; Stubbs, Brendon; Firth, Joseph; Fornaro, Michele; Solmi, Marco (Journal of affective disorders, 2018)
•Dietary inflammatory index (DII®) is a validated measure of inflammatory potential of the diet.•Highest DII® quartile is associated with incident depressive symptoms as defined by CES-D score ⩾16 after a follow-up of 8 years in subjects at risk of arthritis (HR: 1.24; 95% CI: 1.01–1.52; p = 0.04).•Analyses were adjusted for 10 potential confounders at baseline, included age, BMI, baseline CES-D score.•This is the first longitudinal study assessing the association between DII® and depressive symptoms in an American population. Diet is a common source of inflammation, and inflammation is associated with depression. We examined the association between the dietary inflammatory index (DII®), a validated measure of inflammatory potential of the diet, and risk of depression in a cohort of older North American adults. This longitudinal study, with a follow-up of 8 years, included 3648 participants (1577 males, 2071 females; mean age: 60.6 years) with/at risk of knee osteoarthritis. DII® scores were calculated using the validated Block Brief 2000 Food-Frequency Questionnaire. Center for Epidemiological Studies Depression-20 scale was used to define depressive symptoms. The relationship between baseline DII® score and incident depression was assessed through Cox's regression analysis, adjusted for potential confounders, and reported as hazard ratios (HRs). In total, 837 individuals (310 men and 527 women) developed incident depressive symptoms over the course of 8 years. Participants in the most pro-inflammatory group (quartile 4) had approximately 24% higher risk of developing depressive symptoms compared to subjects with the most anti-inflammatory diet (HR: 1.24; 95% CI: 1.01–1.53; p = 0.04). These results suggest that a pro-inflammatory diet may be associated with higher incidence of depressive symptoms in a cohort of older Americans. Transitioning to a more anti-inflammatory diet may reduce depression risk.